2019
DOI: 10.1002/jum.14993
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Neck Mass Point‐of‐Care Ultrasound by Pediatric Emergency Physicians

Abstract: Objectives Neck masses are a common reason for presentations to the pediatric emergency department (PED). We sought to determine the agreement and time difference between point‐of‐care ultrasound (POCUS) imaging by pediatric emergency physicians compared to radiology department imaging for children with neck masses in the PED. Methods We performed a retrospective study of patients aged 0 to 18 years presenting to our tertiary PED who received both POCUS by a pediatric emergency physician and radiology departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Interestingly, pediatricians ranked neck (lymph node vs abscess), advanced abdominal (appendicitis, intussusception, hypertrophic pyloric stenosis, cholecystitis) among the most useful diagnostic applications, studies which tend to be considered more advanced by POCUS experts [ 12 , 16 ]. While the POCUS literature for pediatric appendicitis [ 2 , 38 ] and intussusception [ 39 , 40 ] is growing, there is currently limited evidence to support the use of POCUS for differentiation of neck masses [ 41 43 ]. Constipation was also ranked as a useful diagnostic application by pediatricians; however, there are currently only a handful of studies on the validity of measuring transrectal diameter in the diagnosis of pediatric constipation [ 44 – 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pediatricians ranked neck (lymph node vs abscess), advanced abdominal (appendicitis, intussusception, hypertrophic pyloric stenosis, cholecystitis) among the most useful diagnostic applications, studies which tend to be considered more advanced by POCUS experts [ 12 , 16 ]. While the POCUS literature for pediatric appendicitis [ 2 , 38 ] and intussusception [ 39 , 40 ] is growing, there is currently limited evidence to support the use of POCUS for differentiation of neck masses [ 41 43 ]. Constipation was also ranked as a useful diagnostic application by pediatricians; however, there are currently only a handful of studies on the validity of measuring transrectal diameter in the diagnosis of pediatric constipation [ 44 – 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies ( n = 27 and n = 75) evaluated EP PoCUS diagnostic accuracy on paediatric soft-tissue neck masses and found a Cohen’s kappa coefficient when compared to the final diagnosis of 0.69 (95% CI 0.44–0.94) and 0.71 (0.60–0.83), respectively [184, 185].…”
Section: Resultsmentioning
confidence: 99%
“…POCUS is being increasingly utilised as part of the evaluation for the infant, child or young person presenting to the PED with an undifferentiated neck mass, as both a tool for aiding decision making and for streamlining patient flow. Studies have demonstrated the benefits it provides in terms of both diagnostic accuracy and an overall shorter length of stay in the PED [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%